(untitled) (Research, Society and Development, 2021)
We evaluated performance, nutrient balance, nitrogen balance, and serum parameters in pigs in the nursery phase raised in environmental conditions above the thermoneutral zone that were fed with diets containing various levels of crude protein (CP). A total of 15 barrows (22.75 ± 1.58 kg) were housed in metabolism pens and distributed in a completely randomized design with three treatments: 15.5%, 18.3%, and 21.0% of CP, designated T15, T18, and T21, respectively. There was a gradual increase of temperature over the first three days from 25 to 29.1 ± 2.3 °C. From d18 to d20 of the experiment, pigs received the same diet (18% CP) and thermoneutral conditions were reestablished (22.9 ± 1.9 ºC). There were higher values of urinary, excreted, and absorbed nitrogen in T21, followed by T18 and T15. Blood urea levels were higher in treatments with higher protein levels. On d4 (adaptation period), cholesterol levels were higher in the T15 group than in the T21 group, antioxidant power of iron reduction values were lower in the T18 group than the T21 group. Advanced oxidation protein products (AOPP) on day 16 were higher in the T15 group, associated with the accumulation of heat stress and lower CP diets. Similar results were obtained for T18 with higher AOPP values on d16 than on d8 and d12. However, there were greater AOPP values in the T21 group on d20 (when the CP level was reduced to 18%) than on d8. Amino acid supplementation and reduction of CP in the diet to levels of 15.5% in piglets raised above the thermoneutral zone improved the use of CP. Furthermore, 15.5% of CP in the diet reduced the excretion of urinary nitrogen. The N-retention was not affected by dietary CP level, using the ideal protein concept. The use of 21%-CP in the diet efficiently avoided exacerbation of protein oxidation for pigs raised above thermoneutrality.